2015
DOI: 10.5551/jat.25809
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of Anaerobic Training on Paraoxonase-1 Enzyme (PON1) Activities of High Density Lipoprotein Subgroups and Its Relationship with PON1-Q192R Phenotype

Abstract: Aim: Paraoxonase-1 (PON1) is an antiatherosclerotic enzyme located on high-density lipoprotein (HDL). The effects of anaerobic exercise on PON1 activity are unknown. Here we investigated the effects of anaerobic judo training on three different activities of same PON1 enzyme (TDPON1), including basal PON1, salt-stimulated PON1 (SPON1), and arylesterase (AE) activities, of serum, HDL, and HDL subgroups (HDLs; HDL and its subgroups) and its relationship with PON1-Q192R phenotype (PON1P). Methods: Our study inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…It has been demonstrated that the plasma PON1 activity is elevated in athletic adolescents who engage in regular physical activity, and in football players three days after a tournament [7,15]. In addition, five months of anaerobic training induced an elevation in the circulating PON1 activity [83]. Moreover, the PON1 activity was found to have increased following a single maximal exercise; and this effect was much more pronounced in active than in sedentary subjects [63,64].…”
Section: Paraoxonase 1 Myeloperoxidase and Physical Activitymentioning
confidence: 83%
“…It has been demonstrated that the plasma PON1 activity is elevated in athletic adolescents who engage in regular physical activity, and in football players three days after a tournament [7,15]. In addition, five months of anaerobic training induced an elevation in the circulating PON1 activity [83]. Moreover, the PON1 activity was found to have increased following a single maximal exercise; and this effect was much more pronounced in active than in sedentary subjects [63,64].…”
Section: Paraoxonase 1 Myeloperoxidase and Physical Activitymentioning
confidence: 83%
“…Tomas et al reported an opposite effect of exercise training on PONA according to PON1-192 polymorphism 39 ) . A recent report with Turkish national judoists showed that an anaerobic judo training increased significantly PONA, AREA, and HDL-C, and that interaction of PON1-192 polymorphism was seen in not AREA but PONA 33 ) . In addition to genetic factors, regulation of PON1 activity is affected by environmental factors such as anxiety 40 ) , oxidative stress 41 ) , and inflammation 42 ) .…”
Section: Discussionmentioning
confidence: 96%
“…Table 5 shows limited studies that investigated the effects of exercise training on quantity of HDL and HDL function (CEC and/or PON1) 13 , 24 33 ) . These inconsistent results may be partially due to differences in studied population, HDL-C levels at baseline, exercise status, and concomitant therapy such as diet and medication.…”
Section: Discussionmentioning
confidence: 99%
“…There is now substantial body of evidence suggesting that anaerobic (8) and aerobic exercise trainings at short and long duration (4, 7) are significant factors against atherosclerosis through increasing antioxidant factors. Furthermore, PON1 is a calcium-dependent esterase (4), bound to the surface of HDL (5), and acts as an antioxidant enzyme (2,6).…”
Section: Discussionmentioning
confidence: 99%
“…In this context, it has been shown that long-term aerobic (4) and anaerobic (8) exercise trainings increase PON1 activity and HDL levels in sedentary (4) and active females (8), respectively. In addition, an increased PON1 activity and HDL levels has been revealed following short-term exercise training in football players (7).…”
Section: Introductionmentioning
confidence: 99%